IMPLEMENTASI 2 FACTOR AUTHENTICATION DAN MONITORING TRANSACTION PADA APLIKASI PEMESANAN JASA FOTOGRAFI DAN VIDEOGRAFI DI PRIMAPICTURES - Putra Hilmana, Primarazaq Noorshalih; Abdul Razak, Rizky Septiana; Rizki, Ikhsan Nurul; Afrianto, Irawan (INFOKOM, 2024)
The continuous advancement of information technology has brought both positive impacts and new challenges to system administrators. The universal access and ease of technology have provided opportunities for misuse by malicious actors. Security within website platforms, as a fundamental component of information technology, has become an increasingly critical concern. This research proposes the implementation of an additional security mechanism in the form of Two-Factor Authentication (2FA) to enhance security levels in electronic transactions (E-Payment). We applied this system to the Small and Medium Enterprise (SME) Primapictures, which offers photography and videography services. The descriptive analysis method was used to depict relevant facts and information. Test results indicate successful implementation of 2FA and a monitoring mechanism for orders within the system. The 2FA implementation reduces the risk of phishing attacks and enhances security during login. The monitoring mechanism provides swift responses to suspicious behavior. Conclusions and recommendations from this research provide guidance for further developments in securing online transactions.